2012
DOI: 10.1039/c1dt11256b
|View full text |Cite
|
Sign up to set email alerts
|

Protonolysis of [(iPrO)TiMo5O18]3: access to a family of TiMo5Lindqvist type polyoxometalates

Abstract: The tetra-n-butylammonium (TBA) salts of [((i)PrO)TiMo(5)O(18)](3-) 1 and [((i)BuO)TiMo(5)O(18)](3-) 2 were prepared by hydrolysis of mixtures of (TBA)(2)[Mo(2)O(7)], (TBA)(4)α-[Mo(8)O(26)] and Ti(OR)(4) (R = (i)Pr or (i)Bu) in acetonitrile. Treatment of (TBA)(3)1 with alcohols ROH afforded primary and tertiary alkoxide derivatives [(RO)TiMo(5)O(18)](3-) (R = Me 3, (t)Bu 4), whilst aryloxides [(ArO)TiMo(5)O(18)](3-) were prepared by reacting 1 with phenols ArOH (Ar = C(6)H(4)Me-4 5, and C(6)H(4)CHO-2 6). Oxo-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The synthesis of POM-based hybrids by the use of ligand exchange of acetate ligands in TMSPs has never been reported. , …”
Section: Resultsmentioning
confidence: 96%
“…The synthesis of POM-based hybrids by the use of ligand exchange of acetate ligands in TMSPs has never been reported. , …”
Section: Resultsmentioning
confidence: 96%
“…Coyle et al reported a series of polyoxomolybdates formed from protonolysis of [(iPrO)TiMo 5 O 18 ] 3À [116]. 17 O NMR was used to characterise the molecules in solution and revealed the relative basicities of the complexes, which was attributed to the electron donating ability of the heteroatomligand unit.…”
Section: Solution Dynamics Of Nanometer-sized Aqueous Cluster Ionsmentioning
confidence: 99%
“…Mixed-metal alkoxides are often seen as suitable precursors, undergoing thermal decomposition to oxides under extremely mild conditions, most often in the range 150−180 °C. 13 Even the reports on bimetal titanium−molybdenum alkoxide derivatives appeared very scarce in the literature, with only two compounds, ( n Bu 4 N) 3 [( i PrO)TiMo 5 O 18 ] 14,15 and [{Ti 4 Mo V 2 O 8 (OEt) 10 } 2 ], 16 having compositions not corresponding to that of the target oxide phase. We saw therefore as our aim to develop synthetic approaches and produce structural characterization for bimetallic titanium−molybdenum alkoxides with a 1:1 composition, utilize them in the synthesis of a TiMoO 5 material, and finally, investigate its structure and electrochemical properties to verify its potential applicability as an anode material for Li ion batteries.…”
Section: ■ Introductionmentioning
confidence: 99%